RESULTS OF THE TECHNICAL INSPECTION OF THE FOUNDATION SLAB OF THE PUBLIC BUILDING IN HORODOTSKA STREET, HOUSE 2 IN THE CITY OF LVIV - Burchenia С.; Famuliak Ю.; Vikhot С.; Hrytsyna О. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2024)
A real estate object should be correctly used and its technical conditions should be assessed in order to ensure its reliability. One can establish and assess the technical conditions of the structural system of the object, engineering systems and the surrounding environment due to building inspection. As a result, one can detect defects in structures, prevent collapse, and carry out work on the necessary repairs on time, which will significantly increase its further exploitation. The article presents the results of the inspection of the office building foundation and calculates the load-bearing capacity and deformability of the foundation slab, the reinforcement of which has been partially damaged due to long-term exploitation of the building. Concerning the results of the theoretical calculations carried out in the software package MONOMAKH-SAPR 2013, it is believed that the load-bearing capacity of the foundation slab is provided. However, the calculation of the second group of limit states showed that the deformability of the plate is greater than the maximum allowable values. This caused uneven subsidence of various parts of the slab and the appearance of cracks in the building walls. Technical conditions of the foundation is unsuitable for normal exploitation (category of technical condition – «3»). The place of dismantling the part of the foundation slab should be urgently eliminated by restoring the concrete layer and installing a groove under the K-7 column with the installation of reinforcement frames of appropriate cross-sections with their inclusion in work with both the column and the foundation slab. In places where cracks in the foundation slab are opened, it is necessary to install water resistant plywood stamp and monitor their opening. However, such solution is recommendatory and it is required to perform a detailed design work in the process of preparing design and estimate documentation for the building reconstruction.